Comprehensive profiling of lysine acetylation suggests the widespread function is regulated by protein acetylation in the silkworm, Bombyx mori. Issue 18 (2nd July 2015) - Nie, Zuoming; Zhu, Honglin; Zhou, Yong; Wu, Chengcheng; Liu, Yue; Sheng, Qing; Lv, Zhengbing; Zhang, Wenping; Yu, Wei; Jiang, Caiying; Xie, longfei; Zhang, Yaozhou; et al.
Abstract : Lysine acetylation in proteins is a dynamic and reversible PTM and plays an important role in diverse cellular processes. In this study, using lysine‐acetylation (Kac) peptide enrichment coupled with nano HPLC/MS/MS, we initially identified the acetylome in the silkworms. Overall, a total of 342 acetylated proteins with 667 Kac sites were identified in silkworm. Sequence motifs analysis around Kac sites revealed an enrichment of Y, F, and H in the +1 position, and F was also enriched in the +2 and –2 positions, indicating the presences of preferred amino acids around Kac sites in the silkworm. Functional analysis showed the acetylated proteins were primarily involved in some specific biological processes. Furthermore, lots of nutrient‐storage proteins, such as apolipophorin, vitellogenin, storage proteins, and 30 K proteins, were highly acetylated, indicating lysine acetylation may represent a common regulatory mechanism of nutrient utilization in the silkworm. Interestingly, Ser2 proteins, the coating proteins of larval silk, were found to contain many Kac sites, suggesting lysine acetylation may be involved in the regulation of larval silk synthesis. This study is the first to identify the acetylome in a lepidoptera insect, and expands greatly the catalog of lysine acetylation substrates and sites in insects.